The associative behaviour of silky sharks, Carcharhinus falciformis, with floating objects in the open ocean - Filmalter, John David (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2015)
The silky shark Carcharhinus falciformis forms the primary elasmobranch bycatch in tuna purse seine fisheries using fish aggregating devices (FADs) in all of the world's tropical oceans. Its life-history traits of slow growth, late maturation and low fecundity make it vulnerable to over exploitation, as is apparent from historical bycatch trends. Very little is known about the associative behaviour of this species with floating objects, information which is essential in formulating effective mitigation and management measures. This study aims to address this knowledge gap through the use of various electronic tagging techniques in conjunction with dietary analysis. Dietary data were collected from 323 silky sharks incidentally caught at FADs. Approximately 40 percent of the diet consisted of prey associated with FADs while the remaining 60 percent were non-associated species of crustaceans, cephalopods and fishes. These results suggest that the associative behaviour is not primarily driven by trophic enhancement, but is likely a combination of predator avoidance, social interactions and feeding. Fine-scale behavioural data from silky sharks associated with drifting FADs were collected through the use of acoustic telemetry techniques. Acoustic tags were implanted into 38 silky sharks (69- 116 cm TL) at eight FADs. FADs were equipped with satellite linked acoustic receivers and abandoned to drift freely. Presence/absence and swimming depth data were telemetered via the Iridium satellite system. A total of 300 d of behavioural data were collected from 20 tagged individuals. Individuals remain associated with the same FAD for extended periods (min = 2.84 d, max = 30.60 d, mean = 15.69 d). Strong diel patterns were observed in both association and swimming depth. Typically individuals moved away from FADs after sunset and return later during the night, then remain closely associated until the following evening. Vertical behaviour also changed around sunset with sharks using fairly constant depths, within the upper 25 m, during the day and switching to rapid vertical movements during the night, with dives in excess of 250 m recoded. Broader scale movement behaviour was investigated using pop-up archival satellite tags (PSATs). Tags were deployed on 46 silky sharks (86-224.5 cm TL) for a total of 1495 d. Light data were used to calculate geolocation estimates and reconstruct the sharks' trajectories. Movement patterns differed between animals and according to deployment duration. Several extensive horizontal movements were observed, with an average track length of 3240 km during an average tag deployment of 44.02 d. Horizontal movement patterns were found to correlate very closely with drift patterns of FADs. Consequently, it appears that the movement behaviour of juvenile silky sharks is strongly influenced by the movement of drifting FADs in this region. Ghost fishing of silky sharks through entanglement in FADs was also investigated using data derived from PSATs as well as underwater visual censuses. Thirteen per cent of the tagged sharks became entangled in FADs and entangled sharks were observed in 35 percent of the 51 FADs surveyed. Using this information in conjunction with estimated time that sharks remained entangled in the FAD (from depth data from PSATs), and scaling up according to estimates of FAD numbers, it was found that between 480 000 and 960 000 silky sharks are killed annually in this manner in the Indian Ocean. Subsequent management measures in this region prevent the deployment of FADs with netting that could lead to entanglement. Overall, floating objects appear to play a significant role in the juvenile life stages of silky sharks in this region. While their association with floating objects is clearly advantageous in an evolutionary sense, under current tuna fishery trends, this behaviour is certainly detrimental for the population.
Keywords: Silky shark; Silky shark -- Behavior; Silky shark -- Marking; Silky shark -- Food; Tuna fisheries -- Bycatches; Fish aggregation devices; Underwater acoustic telemetry; Fish tagging